Food waste quantification and characterization in tourism site: A circular economy framework for on-site treatment design - Sasongko, Pramono; Susilo, Bambang; Suhartini, Sri; Sasongko, Nugroho Adi (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Tourism destinations in Indonesia generate food waste in significant number and contribute to 39.78% of total national food waste (FW). However, characterization data for bioprocess applications and evaluations of waste processing remains limited. This study aimed to quantify and characterize food waste from tourism destinations to assess baseline conditions for circular economy and bioprocess implementation. FW was systematically collected and analysed from Jatim Park 2 tourism facilities over Oktober 2024 to January 2025. Food waste generation rates, physical composition, and chemical properties were determined. Existing waste management framework assessed using observational method and stakeholder interviews. Average of 89.2kg/day food waste was generated from 1 main restaurant and 16 food seller in Jatim Park 2 area and predicted to increase up to 121.5kg/day in weekend or holiday. Average moisture content was 72.71%, total solid of 27.29%, and C/N ratio of 46.40. Existing waste processing was limited to collect and transport from waste collection point to waste storage point only. Furthermore, external contractors were contracted to provide waste and FW disposal services. Unfortunately, their partners do not have sufficient disposal service capacity to handle the volume of waste and FW produced. This inadequacy results in the accumulation of waste and FW to a significant volume. In general, the results indicate that tourism FW represent significant untapped resources. The baseline data provides foundation for suitable FW management strategies. Implementation of circular economy could transform FW streams into valuable products contributing to sustainable tourism development.